Diversification of signal identity and modus operandi of the Haemophilus influenzae PAS-less ArcB sensor kinase. - Adrián F Alvarez; Antonio de Jesús Santillán-Jiménez; Eder Flores-Tamayo; Juan L Teran-Melo; Oscar J Vázquez-Ciros; Dimitris Georgellis (PLoS ONE)
Bacteria employ two-component signal transduction systems (TCS) to sense environmental fluctuations and adjust their cellular functions. The Arc TCS is crucial for facultative anaerobes as it enables adaptation to varying respiratory conditions. The Escherichia coli ArcB detects redox changes through two cysteine amino acid residues within its PAS domain. However, the ArcB homologs from most bacteria belonging to the Pasteurellaceae family, lack the entire PAS domain, and in consequence the two regulatory cysteine amino acid residues. In this study, we show that the PAS-less ArcB of Haemophilus influenzae regulates its activity via a cysteine-independent mechanism, and we provide data suggesting that it responds to metabolic signals rather than redox cues. Thus, these two ArcB orthologs sense distinct signals and their regulatory mechanism rely on different molecular events. Our findings reveal divergent evolutionary trajectories of these ArcB homologs, despite the overall conservation of protein components, providing an example of how evolution has shaped different sensing strategies in bacteria.